Penerapan Kampanye Edukasi Perilaku Konsumtif Remaja Usia 17-21 Tahun Melalui Media Sosial - Najwa Aulia Safinka; Nugroho Widya Prio Utomo (VisArt: Jurnal Seni Rupa dan Design, 2025)
In Indonesia, the use of social media has grown rapidly and become a digital era. One of the phenomena that emerged as a result of the rapid development of social media is consumer behavior that encourages teenagers to shop excessively or without planning. In this study, the method used was a qualitative method with data collection through observation, interviews, and literature studies. The results of the study showed that consumer behavior among teenagers is greatly influenced by social factors and digital media. This social education campaign was able to increase adolescent awareness of the impact of consumer behavior and encourage the development of wiser and more responsible consumption habits. Through this campaign media, it is hoped that it will be able to provide education with the aim of reducing consumer behavior for teenagers aged 17-21 years through social media